Hospital Vertical Integration Into Subacute Care as a Strategic Response to Value-Based Payment Incentives, Market Factors, and Organizational Factors: A Multiple-Case Study - Tory H. Hogan PhD; Christy Harris Lemak PhD, MHA; Nataliya Ivankova PhD, MPH; Larry R. Hearld PhD, MBA, MSA; Jack Wheeler PhD, MA; Nir Menachemi PhD, MPH (SAGE Publishing, 2018)
This study explores the extent to which payment reform and other factors have motivated hospitals to adopt a vertical integration strategy. Using a multiple-case study research design, we completed case studies of 3 US health systems to provide an in-depth perspective into hospital adoption of subacute care vertical integration strategies across multiple types of hospitals and in different health care markets. Three major themes associated with hospital adoption of vertical integration strategies were identified: value-based payment incentives, market factors, and organizational factors. We found evidence that variation in hospital adoption of vertical integration into subacute care strategies occurs in the United States and gained a perspective on the intricacies of how and why hospitals adopt a vertical integration into subacute care strategy.